(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was carried out to test the effect of water soaking ofseeds of date palm ( P. dactylifera L.) as a pre-empryo excision treatment,on in vitro culture of zygotic empryos. The objective was optimization oforganogenic callus formation. Mature seeds of “Barakawi” and “MishrigWad Laggi” date palm cultivars were used as sources of embryos.Durations of 0- up to 9-days of seed water soaking, prior to embryoexcision and culture, were tested. Murashige and Skoog (1962) mediumwas used as basal medium. The cultures responded positively to the watersoaking treatments and resulted in the organogenic responses of swelling,germination, callus and adventitious roots formation were obtained. Themagnitude and type of response varied with cultivar and soaking duration.All water soaking treatments increased the measured responses relative tothe control. The results showed that a 6-day soaking treatment wasoptimal for all measured responses compared with the other periods ofsoaking tested. Calli formation in 6-day water soaking treatment were50% and 70% for “Barakawi” and “Mishrig Wad Laggai” ,respectively.However, increasing the soaking duration beyond the 6-day had a markednegative effect on morphogenic response regardless of cultivar. The bestresults for all measured parameters were obtained with embryos of“Mishrig Wad Laggi” compared with embryos excised from “Barakawi”.It seems that soaking date palm seeds in water prior to embryo excisionplay an important role, in enhancing morphogenic response and callusformation in date palm tissue culture.